2002
DOI: 10.1093/ije/31.5.978
|View full text |Cite
|
Sign up to set email alerts
|

The risk of aseptic meningitis associated with the Leningrad-Zagreb mumps vaccine strain following mass vaccination with measles-mumps-rubella vaccine, Rio Grande do Sul, Brazil, 1997

Abstract: Vaccination with the L-Z strain of mumps vaccine as part of a mass campaign was associated with a significantly increased risk of aseptic meningitis. Decisions about type of mumps vaccine and mumps vaccination strategies must consider vaccine safety issues in addition to other criteria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0
4

Year Published

2002
2002
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(20 citation statements)
references
References 10 publications
2
14
0
4
Order By: Relevance
“…84 SAEFI systems constitute an excellent instrument for maintaining the credibility of such campaigns, 112 as well as an opportunity to study rare AEFIs, given that the large number of vaccines administered in a short period of time increases the sensitivity of surveillance. 4,29,30,35,93 However, vaccination campaigns can potentially favor an increase in the perception of the risk associated with vaccination, 30 and may lead to an increase in programmatic errors, given that teams that participate in such campaigns may be less experienced. 36,84,112 Novel technologies, such as the use of bar-coded vaccine vials, allow for greater accuracy, easier registration of administered doses, and better identifi cation of the vaccine batch used.…”
Section: Strategies To Improve the Accuracy Of Saefi Systemsmentioning
confidence: 99%
“…84 SAEFI systems constitute an excellent instrument for maintaining the credibility of such campaigns, 112 as well as an opportunity to study rare AEFIs, given that the large number of vaccines administered in a short period of time increases the sensitivity of surveillance. 4,29,30,35,93 However, vaccination campaigns can potentially favor an increase in the perception of the risk associated with vaccination, 30 and may lead to an increase in programmatic errors, given that teams that participate in such campaigns may be less experienced. 36,84,112 Novel technologies, such as the use of bar-coded vaccine vials, allow for greater accuracy, easier registration of administered doses, and better identifi cation of the vaccine batch used.…”
Section: Strategies To Improve the Accuracy Of Saefi Systemsmentioning
confidence: 99%
“…Some states had to conduct mass vaccination campaigns, and the states used two of the MMR vaccines that we had studied, vaccine A and vaccine C. Thousands of doses were applied in a short period of time. After the campaigns, there was a significant increase in post-vaccination adverse events, among them many cases of aseptic meningitis (22,23). The estimated risk of aseptic meningitis found associated with vaccine A in Rio Grande do Sul was 1 case per 3 390 applied doses (22).…”
Section: Discussionmentioning
confidence: 99%
“…After the campaigns, there was a significant increase in post-vaccination adverse events, among them many cases of aseptic meningitis (22,23). The estimated risk of aseptic meningitis found associated with vaccine A in Rio Grande do Sul was 1 case per 3 390 applied doses (22). In the city of Salvador, Bahia, the risk associated with vaccine C was 1 case per 14 000 applied doses (23).…”
Section: Discussionmentioning
confidence: 99%
“…Despite some safety concerns reported from Brazil, the preparation is believed to be safe, as subsequent studies have reported that the rate of serious adverse events following this extensively used preparation is low [22][23][24][25][26][27]. This observation was supported by the World Health Organization and individual authors [11,28,29].…”
Section: Introductionmentioning
confidence: 96%